SIZE EFFECT OF HYBRID LEARNING ON STUDENTS' SCIENCE LITERACY - Ni'mah Wahyuni; Achmad Ridlowi; Dharma Gyta Sari Harahap; Tomi Apra Santosa; Abdul Rahman (Adisam Publisher, 2023)
This study aims to determine the effect size value of hybrid-based learning on science literacy students. This type of research is meta-analysis research. The data sources in this study came from 12 national and international journals published in 2018-2023. The search process data sources through Google Scholar, ERIC, and ScienceDirect databases. The word The keywords for the data search are